An efficient sequential method for enhanced landfill leachate treatment and detoxification: Electrocoagulation/permanganate, peroxymonosulfate-based process, and electro-peroxone - Hosseinikhah, Maryam; Ghalebizade, Mohamad; Hassani, Aydin; Behzadian, Kourosh; Wacławek, Stanisław; Lin, Kun-Yi Andrew; Ghanbari, Farshid (Journal of environmental management, 2025)
This study investigates the electrocoagulation/permanganate (EC/PM) process as a pre-treatment, followed by UV-activated peroxymonosulfate (PMS) and electro-peroxone (EP) treatments. This sequence is designed to effectively mineralize organic matter. Notably, PM was integrated into the EC process for the first time to enhance removal efficiency. The iron sludge generated from the EC/PM process (sludge-derived electrocoagulation; SDEC) was repurposed as a cost-effective source of iron oxide in the PMS/SDEC/UV treatment. Treatment optimization was achieved by adjusting the main operating parameters. A comprehensive analysis was conducted to assess the biodegradability and toxicity of the leachate post-treatment, including measurements of COD, BOD, TOC, ammonia levels, average oxidation state, biodegradability, organic carbon content, and spectroscopic methods. The results demonstrated substantial removal efficiencies across the treatment stages, with 98.9 % for COD, 94.9 % for BOD, 96.4 % for TOC, and 97.7 % for ammonia. Spectroscopic changes indicated that the leachate was broken down into smaller, more oxidized, and highly acidic molecules with an increased aliphatic structure while effectively eliminating aromatic compounds. The BOD5/COD ratio improved to 0.55, indicating that the treated leachate is suitable for biological treatment processes with significantly reduced toxicity. Overall, the sequence of treatment processes yielded promising results.
Keywords: Electro-peroxone; Water Pollutants, Chemical; Waste Disposal, Fluid; odpad tekutý - odstraňování; Sequential treatment; Peroxides; peroxidy; Permanganate; Landfill leachate; chemické látky znečišťující vodu; Electrocoagulation; Peroxymonosulfate